A similar correction mechanism in slow and fluent readers after suboptimal landing positions - Gagl, Benjamin; Hawelka, Stefan; Hutzler, Florian (Frontiers in Human Neuroscience, 2014)
The present eye movements study investigated the optimal viewing position (OVP) and inverted-optimal viewing position (I-OVP) effects in slow readers. The basis of these effects is a phenomenon called corrective re-fixations, which describes a short saccade from a suboptimal landing position (word beginning or end) to the center of the word. The present study found corrective re-fixations in slow readers, which was evident from the I-OVP effects in first fixation durations, the OVP effect in number of fixations and the OVP effect in re-fixation probability. The main result is that slow readers, despite being characterized by a fragmented eye movement pattern during reading, nevertheless share an intact mechanism for performing corrective re-fixations. This correction mechanism is not linked to linguistic processing, but to visual and oculomotor processes, which suggests the integrity of oculomotor and visual processes in slow readers.